A Systematic Review on the Mental Health Status of Patients Infected With Monkeypox Virus - Jaleel, Anila; Farid, Ghulam; Irfan, Haleema; Mahmood, Khalid; Baig, Saeeda (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2024)
This study aims to extract and summarize the literature on the mental health status of patients with monkeypox. This review was carried out according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines using different databases and publishers such as Scopus, Sage, ScienceDirect, PubMed, BMJ, Wiley Online Library, Wolters Kluwer OVID-SP, and Google Scholar. The literature review was based on monkeypox and mental health. The year of publication was 2021-2023, during the monkeypox disease period. Data were extracted from opinions, editorials, empirical studies, and surveys. Based on the literature related to the mental status of patients with monkeypox, the following themes and subthemes were identified: anxiety and depression, self-harm and suicidal tendencies, neuropsychiatric symptoms, mental health, social stigma, sex workers, vaccination, and stress-related diseases. A review of monkeypox virus infection studies reveals that 25%-50% of patients experience anxiety and depression due to isolation, boredom, and loneliness. Factors such as infected people, a lack of competence among healthcare professionals, and shame over physical symptoms exacerbate mental insults. The implications of society include increased self-harm, suicide, low productivity, fear of stigmatization, and transmission of infection.